2020
DOI: 10.1021/acs.macromol.0c01381
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Initiated Ring-Opening Metathesis Polymerization: A Method for Synthesizing Polymer-Functionalized Nanoparticles Exhibiting Semicrystalline Properties and Diverse Macromolecular Architectures

Abstract: Polymer-grafted nanoparticles are effective for designing hybrid materials with optimal component dispersion and enhanced material properties. The olefin chemistry accessible through ring-opening metathesis polymerization (ROMP) presents a route to polymer-grafted nanoparticles that possess unique chain architectures and chemical functionality difficult to achieve with common surface-initiated polymerization methods. Here, we show that surface-initiated ROMP (SI-ROMP) from silica nanoparticles ranging from 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 132 publications
1
27
0
Order By: Relevance
“…Before the functionalization, silica surfaces are usually cleaned by the Piranha solution [18,29,33], which generates exposed hydroxyl groups on the surface. Trichlorosilanes (RSiCl 3 ) [29,30] and trialkoxysilanes (RSi(OR) 3 ) [75,76] with olefin groups are often used to react with these hydroxyl groups and so functionalize the surface. It was reported that the trichlorosilanes and trialkoxysilanes were first hydrolyzed to give trihydroxylsilanes (R-Si(OH) 3 ) [75,[77][78][79], which then underwent condensation reactions with the hydroxyl moieties on the surface as depicted in Scheme 4.…”
Section: Substrates and Olefin Anchor Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Before the functionalization, silica surfaces are usually cleaned by the Piranha solution [18,29,33], which generates exposed hydroxyl groups on the surface. Trichlorosilanes (RSiCl 3 ) [29,30] and trialkoxysilanes (RSi(OR) 3 ) [75,76] with olefin groups are often used to react with these hydroxyl groups and so functionalize the surface. It was reported that the trichlorosilanes and trialkoxysilanes were first hydrolyzed to give trihydroxylsilanes (R-Si(OH) 3 ) [75,[77][78][79], which then underwent condensation reactions with the hydroxyl moieties on the surface as depicted in Scheme 4.…”
Section: Substrates and Olefin Anchor Designmentioning
confidence: 99%
“…Trichlorosilanes (RSiCl 3 ) [29,30] and trialkoxysilanes (RSi(OR) 3 ) [75,76] with olefin groups are often used to react with these hydroxyl groups and so functionalize the surface. It was reported that the trichlorosilanes and trialkoxysilanes were first hydrolyzed to give trihydroxylsilanes (R-Si(OH) 3 ) [75,[77][78][79], which then underwent condensation reactions with the hydroxyl moieties on the surface as depicted in Scheme 4. The remaining free hydroxyl groups on the silane molecule can participate in further condensations with the hydroxyl groups on either the silica surface or an adjacent silane, holding the attached olefin molecules onto the surface even more tightly.…”
Section: Substrates and Olefin Anchor Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of SI-ROMP has been increasingly applied in various substrates for the preparation of functional metal materials [32][33][34][35][36][37] and non-metal materials. [38][39][40][41][42][43][44] This polymerization technique can also be applied to the surface modification of GO with the advantage of living, controlled polymerization and easily functionalized monomers to enhance the mechanical stability and antipollution of the composite membrane materials. 45 Qiuping Zhang et al 46 employed SI-ROMP to prepare polymer-grafted GO by fixing Grubbs 1st generation catalysts on the surface of GO to carry out ROMP of norbornene (NBE).…”
Section: Introductionmentioning
confidence: 99%
“…Strategic blending of polymers and inorganic nanoparticles includes “softening” the penalties of mixing. Specifically, treatment of the particle surfaces with ligands, small molecules, or polymers will reduce the enthalpic penalties of mixing within the polymer phase. Furthermore, high functional group density (σ) and the ratio between the degrees of polymerization of the grafted polymer chain ( N ) and the matrix ( P ) (e.g., N / P = α ≥ 0.2) prevent nanoparticle/polymer dewetting. , The compatibilization of polymer-functionalized nanoparticles within homopolymer, binary, and ternary blends, both within bulk phases and at film interfaces, is an active area of research. While these strategies have been effective, surface modification methods tend to be extensive, and the solution blending and annealing processes make the materials challenging to scale. Oftentimes, surface-initiated polymerization on a functional particle surface is required to achieve sufficiently high group density at large enough molecular weights to have entropically favorable surface/matrix interactions. , …”
Section: Introductionmentioning
confidence: 99%